John Archibald Campbell, Southern moderate, 1811-1889 - Saunders, Robert, Jr. (Tuscaloosa, Ala. : University of Alabama Press, 1997)
"The life of John Archibald Campbell reflects nearly every major development of 19th-century American history. He participated either directly or indirectly in events ranging from the Indian removal process of the 1830s, to sectionalism and the Civil War, to Reconstruction and redemption."--BOOK JACKET. "Although not a defender of slavery, he feared that abrupt abolition would produce severe economic and social dislocation. He urged southerners to reform their labor system and to prepare for the eventual abolition of slavery. In the early 1850s he proposed a series of reforms to strengthen slave families and to educate the slaves so as to prepare them for assimilation into society as productive citizens. These views distinguished him from many southerners who steadfastly maintained the sanctity of the peculiar institution."--BOOK JACKET. "In this first full biography of Campbell, Saunders reveals the prevalence of anti-secession views prior to the Civil War and covers both the judicial aspects and political history of this crucial period in southern history."--Jacket.
Includes bibliographical references (pages 267-278) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Campbell, John Archibald, -- 1811-1889.; Campbell, John Archibald, -- 1811-1889; Campbell, John Archibald; Campbell, John Archibald; Judges -- United States -- Biography; Judges; United States; Juges -- États-Unis -- Biographies; LAW -- Government -- Federal; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges; Judges; United States; Biografie; Judges -- United States -- Biography; Biography; Biographies; Biographies; Biographies; collective biographies